The Effects of Policy Change Regarding Health Expenditures on Households Behavior - Hamidreza Izadi (Journal of Evidence Based Health Policy, Management & Economics, 2022)
Background: In order to assess households' socioeconomic level in society, policymakers and government planners nowadays pay close attention to families' access to health services. They calculate the percentage of a household's bundle of consumer goods and services. In this regard, the current study examines and analyzes the household's behavior as a result of the government's policies in changing and determining the share of the household's health expenses from its total consumption expenses. This is to ensure that society is kept at a minimum level of health. Methods: In order to accurately execute health policies and change household behavior, this research studies the share and access of Iranian households to health products and services. The author used a Dynamic Stochastic General Equilibrium model through quarterly data from 1997 to 2020. Results: Findings show that as this share increased, other items' consumption and utility decreased, which ultimately led to a fall in society's total utility according to the definition that utility is a term used as a measure of pleasure or happiness resulting from consuming goods and services. Conclusion: The government and policymakers need to bear some of health expenditures and provide financial support to households until it reaches the desired level. This is to prevent a significant decrease in the level of total utility in society. This decrease is brought on by people's dissatisfaction with spending a larger portion of their expenses on health goods and services.